2014
DOI: 10.1007/s10714-013-1656-0
|View full text |Cite
|
Sign up to set email alerts
|

Particle creation by loop black holes

Abstract: We study the black hole particle production in a regular spacetime metric obtained in a minisuperspace approach to loop quantum gravity. In different previous papers the static solution was obtained and shown to be singularity-free and self-dual. In this paper expanding a previous study of the black hole dynamics we repeat the Hawking analysis which leads to a thermal flux of particles at the future infinity. The evaporation time is infinite and the unitarity is recovered due to the regularity of the spacetime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 78 publications
5
34
0
Order By: Relevance
“…which coincides with the former Expression (11) found out in the references [40][41][42]. From the expression for LQBH temperature, one obtains for the entropy:…”
Section: Quantum Tunneling Radiation From Loop Quantum Black Holessupporting
confidence: 88%
See 2 more Smart Citations
“…which coincides with the former Expression (11) found out in the references [40][41][42]. From the expression for LQBH temperature, one obtains for the entropy:…”
Section: Quantum Tunneling Radiation From Loop Quantum Black Holessupporting
confidence: 88%
“…The temperature and entropy of this kind of black hole are calculated by the use of the tunneling method. These first results presented in [38] replicate those found in the references [40][41][42], where other methods have been used. In this way, it can be demonstrated that the quantum tunneling formalism can be successfully applied to address the thermodynamics of LQBHs, opening a path for a whole range of applications.…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…2 The only exception being the "loop black hole" [52], where the evaporation is shown to happen in an infinite time, leaving no remnant. Infinite evaporation times have also been found in specific singular solutions in the presence of higher-curvature terms [53].…”
Section: Problem Setup and Working Assumptionsmentioning
confidence: 99%
“…The information loss problem has also been discussed in the LQBH's framework. As an important result, the problem of information loss by black holes can be relieved in this scenario [44,46].…”
Section: Loop Quantum Black Holesmentioning
confidence: 99%